Mapping of ecosystem services provided by deadwood islands in managed forests: An application in the Italian Alps - Paletto, Alessandro; Sergiacomi, Carlotta (Ecological Questions, 2026)
Over the past few decades, both scientific community and policy makers focused on ecosystem services provided by forests due to their positive impact on human well-being and quality of life. In literature, there is a broad consensus that assessing and mapping ecosystem services is one of the most demanding challenges to address, but at the same time a key tool for effective forest management. This study aims to develop a method suitable to assess and map ecosystem services provided by deadwood islands located in managed forests. To this end, a geospatial analysis was developed in a case study in Italy to conduct an integrated investigation of ecosystem services provided inside and outside the deadwood islands (timber production, stand stability, outdoor recreation, biodiversity conservation). The innovative nature of this study is that it assessed ecosystem services provided by the deadwood islands within managed forests, an aspect that has not yet been investigated in the international literature. The results showed a positive correlation between the four ecosystem services provided by forests and in particular between: timber production and biodiversity conservation; outdoor recreation and stand stability; biodiversity conservation and stand stability. In addition, the results highlighted that the interventions implemented in the deadwood islands have a positive effect on the biodiversity conservation without compromising the provision of other ecosystem services. From a practical standpoint, the results of this study provide forest managers with insights into the impacts of deadwood islands on a wide range of ecosystem services, not just biodiversity. By doing so, managers can better understand the real impacts of this management system on forests.